PENGARUH PENDAPATAN DAN JUMLAH ANGGOTA RUMAH TANGGA TERHADAP KONSUMSI DAGING BABI DI KELURAHAN RURUKAN 1 KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Wowiling, Rifaldy M; Pandey, J; Rembang, V L.H; Endoh, E K.M. (ZOOTEC, 2020)
EFFECT OF INCOME AND TOTAL FAMILY MEMBER ON PORK CONSUMPTION AT RURUKAN 1 VILLAGE, EAST TOMOHON DISTRICT IN TOMOHOM CITY. Study was conducted to evaluate effect of income and total family member on average pork consumption at Rurukan 1 village, East Tomohon district in Tomohom city. Study was done on November to December 2019, using survey method. Study showed that average pork consumption per month of the family was two kg. Income of family member affected significantly (P<0.01) of pork consumption. In addition, total family member affected significantly (P<0.05) of pork consumption. Therefore, it can be concluded that average pork consumption per family per month reached 2.2 kg, significantly affected by income and total family member at Rurukan 1 village, East Tomohon district in Tomohom city.